PB, SR AND BE-10 ISOTOPIC STUDIES OF VOLCANIC-ROCKS FROM THE NORTHERN MARIANA-ISLANDS - IMPLICATIONS FOR MAGMA GENESIS AND CRUSTAL RECYCLING IN THE WESTERN PACIFIC - Woodhead, J; Fraser, D (1985)
We report Sr and Pb isotope analyses for an extensive suite of volcanic rocks from the N. Mariana arc together with Sr and Pb isotope analyses of sediments from the nearby Mariana and Nauru basins. In addition ten of the most recent volcanic samples were analysed for 10Be. The Sr isotope compositions cluster tightly around 87Sr 86Sr = 0.7035 being slightly but significantly higher than the Pacific ocean floor basalts on either side of the arc and agreeing well with previous data. In contrast, the large number of new Pb isotopic data presented significantly extends the observed range of Pb isotope compositions for volcanic rocks from the Mariana arc to more radiogenic compositions. The concentrations of 10Be were very low (< 0.5 × 106 atom g-1). These new data require either that the Pb and Sr isotopic compositions of the Mariana sub-arc mantle be substantially different from those of the mantle source of ocean floor basalts on either side of the arc, or that the enrichment in radiogenic Pb and Sr relative to the values observed in Pacific ocean floor basalts be related to the subduction process. We prefer the latter hypothesis in which radiogenic Sr and Pb in ocean floor sediments are added to M.O.R.B. type mantle either by direct assimilation of the sediments in partial melts or, more probably, by transfer in a fluid phase into the zone of magma production. The low 10Be concentrations observed suggest the removal of at least the top few metres of sediment during subduction. © 1985.